2018
DOI: 10.1016/j.jvs.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational trial of fusion imaging in infrarenal aneurysms

Abstract: When it is used in simple procedures such as infrarenal aneurysm repair, image-based fusion technology is feasible both in hybrid operating rooms and on mobile systems and leads to an overall 50% reduction in radiation dose. Fusion technology should become standard of care for centers attempting to maximize radiation dose reduction, even if capital investment of a hybrid operating room is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
0
23
0
2
Order By: Relevance
“…Precise graft placement and complete exclusion of the aneurysm sac is the key to successful endovascular repair. CBCT and fusion technology allow better visualization of the 3D aortic sac and its branches which allows precise graft placement at lower radiation doses [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise graft placement and complete exclusion of the aneurysm sac is the key to successful endovascular repair. CBCT and fusion technology allow better visualization of the 3D aortic sac and its branches which allows precise graft placement at lower radiation doses [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…There are clear advantages of using fusion imaging, which allows cannulation of visceral and renal branches without using angiography using the fusion map. This lowers radiation exposure as well as contrast dose used [6,7]. Standard infrarenal EVAR using a mobile C-arm has shown to increase radiation exposure to both the patient and the provider.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a statistically significant difference was found in fluoroscopy time between the image fusion group and control group for complex EVAR (5 studies) [6][7][8][9][10] ; however, there was no significant difference in standard EVAR (5 studies). 6,17,[19][20][21] In addition, Stangenberg et al 21 was the only study reporting a significant fluoroscopy time reduction during standard EVAR, whereas the other 4 studies reported no difference or even an increase in fluoroscopy time as can be deduced from Table 2. Figure 3A shows the pooled results for the fluoroscopy time in standard EVAR procedures, which was not different after image fusion compared to no image fusion (0 minutes, 95% CI −3.7 to 3.6, p=0.98).…”
Section: Fluoroscopy Timementioning
confidence: 96%
“…Figure 3A shows the pooled results for the fluoroscopy time in standard EVAR procedures, which was not different after image fusion compared to no image fusion (0 minutes, 95% CI −3.7 to 3.6, p=0.98). There was significant heterogeneity (Q=19.9, p=0.001; I 2 =75%) in the 5 included studies 6,17,[19][20][21] and the hospital cohort. The MD of the hospital cohort (0 minutes, 95% CI −7.2 to 6.8, p=0.79) was comparable with the meta-analysis subtotal (0 minutes, 95 CI −4.2 to 4.2, p<0.001) during standard EVAR.…”
Section: Fluoroscopy Timementioning
confidence: 99%
“…Einen Messwert von null kann man nicht optimieren. Zur permanenten und verlässlichen Überwachung der Strahlenbelastung für die Körperbereiche, die von der Röntgenschürze Moderne Röntgenanlagen mit Fusionstechnologie, bei der die computertomografische Angiografie des Patienten mit den intraoperativen Bildern fusioniert wird, können deshalb ebenfalls zur Reduktion der Strahlendosis für Patienten und OP-Personal führen [11,12].…”
Section: Diskussionunclassified